MERS-CoV seroconversion amongst Malaysian Hajj pilgrims returning from the Middle East, 2016-2018: results from the MERCURIAL multiyear prospective cohort study - Johari, Jefree; Hontz, Robert D.; Pike, Brian L.; Husain, Tupur; Rusli, Norhayati; Mohd-Zain, Rozainanee; Tiong, Vunjia; Lee, Hai-Yen; Teoh, Boon-Teong; Sam, Sing-Sin; Khor, Chee-Sieng; Loong, Shih-Keng; et al. (Emerging microbes & infections, 2023)
Prospective cohort study to investigate the potential exposure to the Middle East Respiratory Syndrome-Coronavirus (MERS-CoV) following Hajj pilgrims is still very limited. Here, we report the antibody seroconversion study results obtained from successive three years cohort studies (2016-2018) involving the Malaysian Hajj pilgrims returning from the Middle East. A cohort study of Hajj pilgrims from Malaysia enrolled 2,863 participants from 2016-2018, all of whom consented to provide paired blood samples for both pre- and post-Hajj travel to the Middle East. ELISAs and micro-neutralization assays were performed to detect the presence of MERS-CoV IgG antibodies. Sociodemographic data, symptoms experienced during Hajj, and history of exposure to camels or camel products were recorded using structured pre- and post-Hajj questionnaires. A 4-fold increase in anti-MERS-CoV IgG between paired pre-Hajj and post-Hajj serum samples in twelve participants was observed. None of the twelve ELISA-positive sera had detectable levels of virus-neutralizing antibodies. All reportedly had mild symptoms of respiratory symptoms at a certain point during the pilgrimage, implying mild or asymptomatic infections. No association between post-Hajj serum positivity and a history of exposure to camels or camel products was obtained. Findings from the study suggest that serologic conversion to MERS-CoV occurred in at least 0.6% of the Hajj pilgrims returning from the Middle East. Since all the seroconvertants had mild to no symptoms during the sampling period, it highlights the likelihood of occurrence of only low infectivity spillover infections among the Hajj pilgrims.